2007
DOI: 10.1108/14777830710717730
|View full text |Cite
|
Sign up to set email alerts
|

Urban solid waste generation in Port Harcourt metropolis and its implications for waste management

Abstract: PurposeThe purpose of this paper is to examine the impact of rapid population growth due to uncontrolled and unplanned urbanization as it affects environmental degradation through solid waste generation in Port Harcourt Metropolis, which has brought about the problem of solid waste management to city authorities and state governmentDesign/methodology/approachThe study involved the administration of questionnaires to 76 different households with a total population of 393 persons giving an average size of 7 pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 14 publications
1
51
1
Order By: Relevance
“…The amount of waste could aggravate and may both be hard and expensive to manage. In this regard, the management capability of most of the solid waste management systems that may deal with the increasing volume of waste and its changing characteristics in almost all areas has to be necessarily enhanced due to overwhelming overpopulation and economic affluence (Ogbonna et al, 2007). A World Bank study showed that urban areas in Asia spent USD25 million per year on solid waste management, and this figure will increase to USD47 million per year.…”
Section: Table 4 Composition By Volume (L) Of the Solid Wastes Genermentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of waste could aggravate and may both be hard and expensive to manage. In this regard, the management capability of most of the solid waste management systems that may deal with the increasing volume of waste and its changing characteristics in almost all areas has to be necessarily enhanced due to overwhelming overpopulation and economic affluence (Ogbonna et al, 2007). A World Bank study showed that urban areas in Asia spent USD25 million per year on solid waste management, and this figure will increase to USD47 million per year.…”
Section: Table 4 Composition By Volume (L) Of the Solid Wastes Genermentioning
confidence: 99%
“…Here, majority of the wastes were generated from household sources. Accounting for this could be the increasing rate of population growth and economic development in urban areas, which may lead to an increase in wastes generation (Ogbonna et al, 2007;Ramachandra & Bachamanda, 2007). The amount of waste could aggravate and may both be hard and expensive to manage.…”
Section: Table 4 Composition By Volume (L) Of the Solid Wastes Genermentioning
confidence: 99%
“…For an efficient and systematic management of wastes, the essential aspects and interaction between them must be identified and clearly understood. Thus, there is an immediate need to understand and tackle waste at firm, industry, corporation, regional, national and finally at global level (Nabegu 2010;Ogbonna 2007;Khalil & Khan 2009) …”
Section: Socio-economic Aspects Of Waste Generation At Macro Levelmentioning
confidence: 99%
“…This introduction of private companies in waste management became necessary as a result of the degradation of the environment from inefficient waste management practices (Ogu, 2000). Ogbonna et al (2007) reported that in response to the enormous challenges pose by municipal solid waste management, the Government is taking steps to address these problems by engaging local contractors to evacuate waste. Ogu (2000) added that such steps were necessary in order to bring private sector investment into waste management and to enhance service delivery.…”
Section: Introductionmentioning
confidence: 99%